Standard specification for Metallic-Coated, Steel-Woven Wire Fence Fabric (American Society for Testing and Materials, 2005)
This specification covers metallic-coated steel fence fabric having a series of horizontal (line) wires, with vertical (stay) wires either wrapped around the line wire (hinge joint) or fixed with another separate wire to the line wire (continuous stay fixed knot joint), forming rectangular openings.